Uji Aktivitas Analgetik Ekstrak Rimpang Bangle (Zingiber purpureum R.) Pada Tikus Putih Jantan Dengan Metode Writhing Test - Shahira, Iyem; Ningsih, Dwi; Herowati, Rina (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Pain is an unpleasant emotional sensation caused by tissue damage. Bangle rhizome is a plant that can be used to treat pain. The purpose of this study was to determine the analgesic activity of a 96% ethanol extract of bangle rhizome in male white Wistar rats and to determine the most effective dose for producing analgesic effects. Bangle rhizome was extracted by maceration method using 96% ethanol solvent. This study used Writhing test method at 25 male divided into five groupes. Group I as negative control was administered 0,1% CMC, group II as positive control was administered acid mefenamic, group III, IV, and V was administered extract of bangle rhizome. The data obtained from this study were the number of wriggles of the test animals and the reaction time of the test animals' responses (minute). The result of the research showed that extract doses 30,843 mg/200 g BB, 61,686 mg/ 200 g BB, and 123,372 mg/ 200 g BB comparable to the positive control and different from the group given the negative control.. Extract dose 123,372 mg/ 200 gB compare with positive control was indicated that extract doses 123,372mg/ 200 g BB showed the highest analgesic activity.